Cyclooxygenase-1 as a Potential Therapeutic Target for Seizure Suppression: Evidences from Zebrafish Pentylenetetrazole-Seizure Model - Barbalho, Patrícia Gonçalves; Carvalho, Benilton de Sá; Lopes-Cendes, Iscia; Maurer-Morelli, Claudia Vianna (Frontiers in Neurology, 2016)
Cyclooxygenases (COX) -1 and -2 are isoenzymes that catalyze the conversion of arachidonic acid into prostaglandins (PGs). COX-2 and PGs are rapidly increased following seizures and are known to play important roles in the neuroinflammatory process. COX-2 isoform has been predominantly explored as the most suitable target for pharmacological intervention in epilepsy studies while COX-1 remains poorly investigated. In the present study, we evaluated the effects of selective cyclooxygenases (COX) -1 inhibitor or selective COX-2 inhibitor on seizure suppression in the zebrafish pentylenetetrazole (PTZ)-seizure model. Zebrafish larvae were incubated in 5 μM of SC-236 for 24 hours or 2.8 μM of SC-560 for 30 minutes, followed by exposure to 15 mM PTZ for 60 min. Real-time quantitative PCR analysis was carried out to investigate transcription levels of cox1 (ptgs1), as well as to determine cfos levels, used as a marker for neuronal activity. Effects of selective COX-2 or COX-1 inhibitors on locomotor activity response (velocity and distance moved) during PTZ exposure were evaluated using the Danio Vision video-tracking system. Our results showed an inducible expression of the cox1 gene after 60 minutes of PTZ exposure. Cox1 mRNA levels were upregulated compared with the control group. We found that COX-2 inhibition treatment had no effect on zebrafish PTZ-induced seizures. On the other hand, COX-1 inhibition significantly attenuated PTZ-induced increase of locomotor activity and reduced the c-fos mRNA expression. These findings suggest that COX-1 inhibition rather than COX-2 has positive effects on seizure suppression in the zebrafish PTZ-seizure model.